Reversible Removal of Intermixed Shallow States by Light Soaking in Multication Mixed Halide Perovskite Films - Guo, Dengyang (ACS Energy Lett, 2019)
[Image: see text] The highest reported efficiencies of metal halide perovskite (MHP) solar cells are all based on mixed perovskites, such as (FA,MA,Cs)Pb(I(1–x)Br(x))(3). Despite demonstrated structural changes induced by light soaking, it is unclear how the charge carrier dynamics are affected across this entire material family. Here, various (FA,MA,Cs)Pb(I(1–x)Br(x))(3) perovskite films are light-soaked in nitrogen, and changes in optoelectronic properties are investigated through time-resolved microwave conductivity (TRMC) and optical and structural techniques. To fit the TRMC decay kinetics obtained for pristine (FA,MA,Cs)Pb(I(1–x)Br(x))(3) for various excitation densities, additional shallow states have to be included, which are not required for describing TRMC traces of single-cation MHPs. These shallow states can, independently of x, be removed by light soaking, which leads to a reduction in the imbalance between the diffusional motion of electrons and holes. We interpret the shallow states as a result of initially well-intermixed halide distributions, which upon light soaking segregate into domains with distinct band gaps.